A comparative study on counterterrorism act in Malaysia, United States of America and New Zealand / Enda Noratika Nordin…[et al.] - Nordin, Enda Noratika; Amad Saturi, Nur Syarah Syazwan; AB Ghani, Farah Amalina; Ahmad Istihar, Farahiyah (Faculty of Law, 2013)
Terrorism is the act ofviolent with the goal of embedding fear to a certain society. For example a massacre is one of it, genocide is also one of it or even killing out of revenge in a small town that makes the people scared to go out. The terror that the violent acts created will make people surrounded by fear, confusion or even discord. Many people just think that terrorism has always been related to just religious and political motives. But actually it is beyond that. It is true that religious and political goals are one ofthe reasons of creating violent acts but it certainly not the only reason. Terrorists could also act violently because ofrevenge, mental disorder or anger. In Malaysia, in order to combat and curb terrorist activities, the government had enacted the Security Offences (Special Measures) Act 2012. The purpose ofthis research is to study and examine the terrorism Act in Malaysia and to provide recommendation in order to improve the lacunae in the said legislation.